Karma of Cardiovascular Disease Risk Factors for Prevention and Management of Major Cardiovascular Events in the Context of Acute Exacerbations of Chronic Obstructive Pulmonary Disease - Crisan, Liliana; Wong, Nathan; Sin, Don D.; Lee, Hwa Mu (Frontiers in Cardiovascular Medicine, 2019)
There is compelling epidemiological evidence that airway exposure to cigarette smoke, air pollution particles, as well as bacterial and viral pathogens is strongly related to acute ischemic events. Over the years, there have been important animal and human studies that have provided experimental evidence to support a causal link. Studies show that patients with cardiovascular diseases (CVDs) or risk factors for CVD are more likely to have major adverse cardiovascular events (MACEs) after an acute exacerbation of chronic obstructive pulmonary disease (COPD), and patients with more severe COPD have higher cardiovascular mortality and morbidity than those with less severe COPD. The risk of MACEs in acute exacerbation of COPD is determined by the complex interactions between genetics, behavioral, metabolic, infectious, and environmental risk factors. To date, there are no guidelines regarding the prevention, screening, and management of the modifiable risk factors for MACEs in the context of COPD or COPD exacerbations, and there is insufficient CVD risk control in those with COPD. A deeper insight of the modifiable risk factors shared by CVD, COPD, and acute exacerbations of COPD may improve the strategies for reduction of MACEs in patients with COPD through vaccination, tight control of traditional CV risk factors and modifying lifestyle. This review summarizes the most recent studies regarding the pathophysiology and epidemiology of modifiable risk factors shared by CVD, COPD, and COPD exacerbations that could influence overall morbidity and mortality due to MACEs in patients with acute exacerbations of COPD.